2022
DOI: 10.1002/clt2.12172
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the regulation of TGF‐β/Smad and MPK signaling pathway gene expressions by nasal allergen and methacholine challenge test in asthma

Abstract: Background Asthma is a heterogeneous chronic inflammatory disease of the bronchi, the course of which is significantly influenced by extrinsic factors (specific and non‐specific). Methods The aim of this study was to evaluate the effect of these factors represented by nasal allergen challenge (specific factors) and methacholine challenge test (non‐specific) on changes in mRNA expression of genes encoding the TGF‐β (TGF‐β1 and TGF‐β3)‒Smad (mitogen‐activated protein kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The complex thus formed leads to the phosphorylation of the kinase domain of TGFβRI, which in turn results in the activation of the Smad pathway. [9][10][11] This is therefore a targeted pathway for research into Analyses of the functional role of selected TGF-β cytokine homologous molecules conducted so far as part of the pilot study have demonstrated that newly designed peptide inhibitors for the region I inhibit gene expression of Smad-dependent and Smad-independent pathways, which indicates that they are potent to block the TGFβRI/ TGFβRII receptor complex in vitro (Figures 7 and 8, Tables 2-5).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The complex thus formed leads to the phosphorylation of the kinase domain of TGFβRI, which in turn results in the activation of the Smad pathway. [9][10][11] This is therefore a targeted pathway for research into Analyses of the functional role of selected TGF-β cytokine homologous molecules conducted so far as part of the pilot study have demonstrated that newly designed peptide inhibitors for the region I inhibit gene expression of Smad-dependent and Smad-independent pathways, which indicates that they are potent to block the TGFβRI/ TGFβRII receptor complex in vitro (Figures 7 and 8, Tables 2-5).…”
Section: Discussionmentioning
confidence: 99%
“…Expression analysis of the studied genes was performed in the Department of Medical Biochemistry of the Medical University of Lodz, Lodzkie Voivodeship, Poland. 10,[22][23][24] Expression was analyzed for the following genes:…”
Section: Determination Of the Minimum Tgf-β-tgfβri And Tgf-β-stgfβrii...mentioning
confidence: 99%
See 3 more Smart Citations